The Relationship between Defense Patterns and DSM-5 Maladaptive Personality Domains - Granieri, Antonella; La Marca, Luana; Mannino, Giuseppe; Giunta, Serena; Guglielmucci, Fanny; Schimmenti, Adriano (Frontiers in Psychology, 2017)
Aim: Research has extensively examined the relationship between defense mechanisms and personality traits. However, no study to date has explored if specific defenses (alone or in combination) are able to predict dysfunctional variants of personality domains, as conceived in the alternative DSM-5 model for personality disorders. This study aimed to investigate the relationship between defense mechanisms and DSM-5 maladaptive personality domains among adults. Material and Methods: Three hundred twenty-eight adults aged between 18 and 64 years old completed measures on defense mechanisms and maladapive personality domains. Regression analyses were performed to determine which defense mechanisms predicted the maladaptive personality domains of negative affectivity, detachment, antagonism, disinhibition, and psychoticism. Results: According to psychoanalytic literature, results showed that immature defenses positively predicted maladaptive personality domain scores, whereas mature defenses were generally related with better personality functioning. Moreover, different defense patterns emerged as significant predictors of the maladaptive personality domains comprised in the alternative DSM-5 model for personality disorder. Discussion: Our findings support the view that defense patterns represent core components of personality and its disorders, and suggest that an increased use of immature defenses and a reduced use of mature defenses have a negative impact on the development of personality.